A MANAGERIAL VIEW ON TURKISH THEATER: THE ROLE OF THEATER AUDIENCE - (:unkn) unknown (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2018)
Theater managers and owners are parts of the Turkish theater with works they produce through the theaters. Their thoughts and perspectives shape their art and thus shape the country's theatrical approach. The aim of this study is to carry out an analysis on the Turkish theater sector which is accessible to limited scientific sources and to explore the place of theater audiences in the sector and all other important factors related with the subject. In order to achieve this aim, in-depth interviews were conducted with selected four theater representatives. In the light of the interviews with the theater owners and managers, which is a tool to recognize the sector in this study, important topics representing the sector were discovered, such as theater sector in Turkey, trends in the sector, changing locations, the production process, the good play perception, audience analyses, communication systems, audience strategies, strategies for building relationship, theaters'own SWOT analyses, and financial efforts of theaters.
Keywords: theater; audience; arts marketing; arts communication; ARTS; CONSUMPTION; DEMAND; MODEL